2017
DOI: 10.1002/cpim.28
|View full text |Cite
|
Sign up to set email alerts
|

A Real‐Time Cytotoxicity Assay as an Alternative to the Standard Chromium‐51 Release Assay for Measurement of Human NK and T Cell Cytotoxic Activity

Abstract: This unit describes the monitoring and quantification of cellular cytotoxicity using a non-radioactive and real-time cytotoxic assay. The extent of target-cell lysis is monitored over time by imaging and quantifying live fluorescent target cells using a cell-imaging multimode reader. This assay is performed in a 96 well plate in optimized culture conditions at 37°C in the presence of 5% CO . The basic protocol describes natural killer cell-mediated cytotoxic assay that can be adapted to include antibodies bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Developed in 1968, this technique is still the gold standard for evaluation of cytotoxicity but requires handling radioactivity and autologous tumor targets. Interestingly, nonradioactive tests for cytotoxicity are emerging, based on flow cytometry ( 66 ) or microscopy of fluorescent target cells ( 67 ). Another classical way to measure T cell and NK cell cytotoxicity is enzyme-linked immunospot (ELISPOT), a sensitive immunoassay that measures the frequency of cytokine-secreting cells at the single-cell level ( 68 , 69 ).…”
Section: Classical and New Technics Of Immune Monitoringmentioning
confidence: 99%
“…Developed in 1968, this technique is still the gold standard for evaluation of cytotoxicity but requires handling radioactivity and autologous tumor targets. Interestingly, nonradioactive tests for cytotoxicity are emerging, based on flow cytometry ( 66 ) or microscopy of fluorescent target cells ( 67 ). Another classical way to measure T cell and NK cell cytotoxicity is enzyme-linked immunospot (ELISPOT), a sensitive immunoassay that measures the frequency of cytokine-secreting cells at the single-cell level ( 68 , 69 ).…”
Section: Classical and New Technics Of Immune Monitoringmentioning
confidence: 99%
“…When considering the role of NKp30 on Trypanosoma cruzi infections, Hermann et al found that cord blood NK cells from newborns congenitally infected with T. cruzi had a reduced expression of NKp30, which could be due to earlier NK cell activation or to NK cell activity down‐regulation by T. cruzi itself (Hermann et al, 2006). Later work has shown that NK cells were activated in utero , during the first exposure to the parasite and that the foetus response to T. cruzi is an adult‐like one, based on IFN‐γ production by CD8 + T cells and through an IL‐12‐dependent monocyte pathway (Berrien‐Elliott et al, 2015; Fassy, Tsalkitzi, Goncalves‐Maia, & Braud, 2017; Lapteva et al, 2012; Porrata, Inwards, Lacy, & Markovic, 2001).…”
Section: Nkp30 As a Mediator Of Nk Activitymentioning
confidence: 99%
“…While this assay has many limitations, the result distinctly demonstrates whether or not target cells are finally killed (Figure 2) (54). Numerous flow-, colorimetric-, and imaging-based cytotoxicity assays have been touted as possible chromium release assay replacements but no large cohort of primary HLH cases has been validated on any of these platforms (5559). Pending such reports, the chromium release assay is still the only published clinical standard for NK functional studies.…”
Section: Secretory Granule Exocytosis Deficiencymentioning
confidence: 99%